PRE-SERVICE MATHEMATICS TEACHERS METACOGNITIVE BELIEFS AND THEIR EFFECT ON MATHEMATICS ANXIETY - Hendra Kartika; Lessa Roesdiana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
The present study aimed to identify the effects of metacognitive beliefs on mathematics anxiety encompassed by pre-service mathematics teachers’. The intervention role of factors such as positive beliefs was also examined. For this purpose, a total of sixty college students from the mathematics education program of one of the public universities in Indonesia were investigated through cross-sectional surveys. The data of the research were collected through a students’ self-report measure of metacognitive beliefs and mathematics anxiety. The results reveal that although there is no gender difference in metacognitive beliefs, female students are more anxious in mathematics than male students. There are no year levels of difference in metacognitive beliefs and mathematics anxiety. The result shows that metacognitive beliefs have negatively correlated with math anxiety. This study concludes that developing metacognitive beliefs helps pre-service mathematics teachers to effectively overcome mathematics anxiety. Also, enhancing cognitive confidence and controlling negative beliefs about the uncontrollability of thoughts and danger has implications as a treatment to reduce mathematics anxiety.